Political power, resistance to technological change and economic development: Evidence from the 19th century Sweden - Björn Tyrefors Hinnerich; Erik Lindgren; Per Pettersson-Lidbom (Research Institute of Industrial Economics (IFN), 2017)
This paper empirically tests the hypothesis that landed elites may block technological change and economic development if they fear that they will lose future political power (Acemoglu and Robinson (2002, 2006, and 2012). It exploits a plausible exogenous change in the distribution of political power of the landed elites, i.e., a Swedish suffrage reform in 1862 which extended the voting rights to industrialists at the local level. Importantly, the votes were also weighted according to taxes paid. Thus, the higher taxes paid the more votes received. As a result, the landed elites had an incentive to block industrialization and technological progress since they otherwise would be “political losers”. We find that the change in political power from the landed elites to industrialists, through the extension of suffrage rights, lead to more investments in railways, faster structural change, and higher firm productivity. We also find that the change of political power affected both labor coercion and the adaption of labor-saving technologies within the agriculture sector along the lines suggested by Acemoglu and Wolitzky (2011) and Acemoglu (2010). Specifically, we find that is more labor coercion and less investments in labor-saving technologies in areas were landowners have more political power. We also provide evidence that many demographic outcomes were affected by the change in political power. Moreover, we find strong evidence of persistence in both extractive economic and political institutions even after the weighted voting system was abolished and universal suffrage introduced in 1919. Specifically, local governments that were previously political controlled by the landed elites were still using both extractive economic and political institutions (Acemoglu and Robinson (2008)).
Keywords: E22; E23; E24; E62; F15; H41; H52; H53; H70; J10; J21; J22; J23; J24; J31; J32; J41; J43; J47; N10; N33; N53; N63; N73; N93; O10; O14; O15; O18; O33; O40; O52; R10; R42; 330; Economic development and growth; Political institutions; Technological change; Industrialization; Labor coercion; Labor-saving technologies; Persistence of extractive economic and political institutions